2003
DOI: 10.1085/jgp.20028768
|View full text |Cite
|
Sign up to set email alerts
|

On the Conformation of the COOH-terminal Domain of the Large Mechanosensitive Channel MscL

Abstract: COOH-terminal (S3) domains are conserved within the MscL family of bacterial mechanosensitive channels, but their function remains unclear. The X-ray structure of MscL from Mycobacterium tuberculosis (TbMscL) revealed cytoplasmic domains forming a pentameric bundle (Chang, G., R.H. Spencer, A.T. Lee, M.T. Barclay, and D.C. Rees. 1998. Science. 282:2220–2226). The helices, however, have an unusual orientation in which hydrophobic sidechains face outside while charged residues face inside, possibly due to specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
94
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(117 citation statements)
references
References 56 publications
20
94
2
1
Order By: Relevance
“…No corresponding conductance was observed when suction was applied to patches formed from vesicles produced in the absence of channel protein. In general, the electrophysiological features of synthetic Ec-MscL activity closely resemble those observed for recombinant Ec-MscL (24)(25)(26): open-channel conductance of 3 nS; the presence of multiple substates; and the overall sensitivity to suction (24)(25)(26).…”
Section: Multimilligram Quantities Of Channel Protein Were Generated Bymentioning
confidence: 59%
“…No corresponding conductance was observed when suction was applied to patches formed from vesicles produced in the absence of channel protein. In general, the electrophysiological features of synthetic Ec-MscL activity closely resemble those observed for recombinant Ec-MscL (24)(25)(26): open-channel conductance of 3 nS; the presence of multiple substates; and the overall sensitivity to suction (24)(25)(26).…”
Section: Multimilligram Quantities Of Channel Protein Were Generated Bymentioning
confidence: 59%
“…MscL forms an ϳ30-Å nonselective pore and stays open from milliseconds at the activation threshold to seconds at near-saturating tensions (15). The cytoplasmic bundle of the C-terminal segments was predicted to form a stable pre-filter in both open and closed conformations (17), but recent results suggested that it may occasionally disassemble, as frequently firing gain-of-function MscL mutants can pass polypeptides up to 6.5 kDa (18).…”
Section: Opening Of Mscl Creates a Large Stable Pore Accompanied By Pmentioning
confidence: 99%
“…The cytoplasmic domain starts at the end of the TM2 helix, where the RKKEE motif in MscL of E. coli (RKKGE in M. tuberculosis), critical for pH sensing and channel function, is located (57,73). Reinterpretation of the crystal structure originally published by Chang et al (24) revealed that the cytoplasmic C-terminal helices form a five-helix bundle (138) postulated by Anishkin and co-workers (6), where the hydrophobic residues are oriented inward (and not outward, as was incorrectly modeled in the original X-ray structure) in agreement with the EPR spectroscopic study of the closed form of MscL (122). Consequently, the inverted model of the C-terminal domain was adopted in the reinterpreted crystal structure (139).…”
Section: Structure Of Msclmentioning
confidence: 99%